Novelties in Strychnos sect. Breviflorae (Loganiaceae) - Brandão, Ellen Kallyne De Sousa; Rapini, Alessandro (Phytotaxa, 2017)
Floristic studies on the Loganiaceae from the state of Bahia, Brazil, allowed the recognition of a new species of Strychnos, S. nana, which is described and illustrated here. This is one of the few species of the genus inhabiting savannas, and can be promptly recognised by the small habit (< 50 cm high) and leaves (up to 1.1 × 1.1 cm). Besides, we are describing, for the first time, 1) the fruit and seed of S. alvimiana, species published based on sterile material, and 2) the inflorescence and flower of S. atlantica, which was established based on material only with fruits; epitypes are also designed for these two names.